EVALUATION OF THE EFFECTIVENESS OF BLOCKCHAIN TECHNOLOGIES IN THE HIGHER EDUCATION SYSTEM - Anvarova Mukaddas Makhamadjonovna; Khusniddinov Yorqinjon Muhiddin o’g’li (Modern American Journals, 2025)
This article analyzes the implementation of blockchain technologies in the higher education system and evaluates their effectiveness. It highlights how blockchain ensures data security, transparency, and reliability in educational processes. In addition, the article examines international practices and the current situation in the national context, using statistical data to assess the changes observed in institutions where blockchain has been implemented. Special attention is given to identifying the role of blockchain in education, current challenges, and emerging opportunities.
Keywords: Blockchain, higher education, digital technology, data security, education quality assessment.